A Colton kidnapping - Davis, Justine (Coltons of Owl Creek., 2024)
A Colton kidnapping: They had nothing in common Briony, a shy accountant and Greg, a gruff Colton rancher. But after the death of their two best friends, Briony and Greg become uneasy guardians of the couple's two children. When the children's dangerous grandfather tries to gain custody, the two new parents know they must get married to protect their found family. Can Briony and Greg save the children and also their hearts as they grow closer together?